CIVIC CULTURE DIKALANGAN GENERASI MUDA DESA KOTO MAJIDIN DALAM TRADISI NYALABA GELA PEMANGKU ADAT - Wahyuni Putri, Amalina; Tohap Pandapotan Simaremare; Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the civic culture among the younger generation in Koto Majidin Village within the Nyalaba Gela tradition led by traditional leaders. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the declining interest of the younger generation in the Nyalaba Gela tradition is influenced by several factors, including a lack of motivation to understand and participate in traditional activities, the impact of modernization and technological advancement that shifts attention toward social media, and limited involvement of youth in customary events. These conditions lead to a diminished sense of responsibility and belonging toward the preservation of the tradition. Efforts to sustain the continuity of the tradition include strengthening the role of parents in instilling cultural values from an early age and encouraging greater youth participation in customary activities to foster responsibility in preserving the Nyalaba Gela tradition.